Coffee Berry Borer, Hypothenemus Hampei Ferr.: Cultural Control and In Vitro Effects of Kernel Extracts of Azadirachta indica A. Juss. and Thevetia peruviana (Pers.) Schum - Manga Essouma François; Voula Valteri Audrey; Kone Nsangou Abdou Nourou; Mvondo Nganti Dorothée; Ambang Zachée (European Scientific Journal, ESJ, 2021)
The coffee berry borer, Hypothenemus hampei, is one of the most important coffee berry borer pests in the world, reaching attack rates of 10-100% in Cameroon. The objective of this study is to evaluate the efficacy of crop control and the effects of aqueous extracts of Thevetia peruviana kernel powder and aqueous extracts, and oil of Azadirachta indica kernel powder against this insect. Crop control was firstly achieved by sanitary harvesting of bark beetle-infested berries and, secondly, by the installation of a network of home-made pheromone traps. The bark beetles were breeding in the laboratory and tests were also carried out on substitute foodstuffs such as maize and groundnuts. The efficacy of pesticidal plant extracts at four concentrations each was evaluated by direct applications of these on bark beetles and berries. The results showed that the reproduction rate of the borer was 11 times higher with coffee berries than with maize and groundnuts. After the direct treatment of the bark beetles, the aqueous extracts of T. peruviana showed a significantly average efficiency on the mortality of the bark beetles ranging from 0% to 94.9% of bark beetles killed. Oil extracts of A. indica and chlorpyrifos-ethyl (Pyriforce) were more effective against bark beetles with average mortality rates ranging from 78.7 to 100%. After direct treatment of the berries, oil and aqueous extracts of A. indica and chlorpyrifos-ethyl were the most effective treatments causing more than 50% mortality of the bark beetles. Oil of A. indica and aqueous extracts of T. peruviana can therefore be used in the same way as pyriforce in the protection of coffee plants against H. hampei.